Assessment of the Size of Sella Turcica among Nepalese Population by Computed Tomography - Makaju, Gourav; Joshi, Birendra Raj; Chand, Ram Bahadur (Nepalese Journal of Radiology, 2019)
Introduction: The deformity of the sella turcica is often a major clue that an abnormality exists within the cranium, hence a familiarity with the sella turcica anatomy and radiological appearance is important. The aim of this study was to assess the dimension of sella turcica of normal Nepalese people by using computed tomography scan of head and to correlate the dimension with the patient’s age and gender. Methods: This prospective study was performed in a tertiary hospital in Kathmandu. Data were collected over the period of 4 months from June to September 2018 with the total of 73 patients who underwent CT of head. The age and gender of the patients were noted. The dimensions of sella turcica were measured at the predefined three directions: length, depth and antero-posterior diameter of the sella turcica. Results: The sella turcica had a mean length of 8.375mm, AP diameter of 7.029mm, and depth of 10.13mm.The dimensions of the sella turcica increased with age till the age of 80 years and then decreased. Conclusions: This study concluded that the length, AP diameter and depth of the sella turcica vary with respect to age group. The length and depth of sella turcica were higher in males while AP diameter in females.